Family planning amongst the Akha & Khmu : "what type of services is necessary?" : Khua District, Lao PDR : a dissertation presented in partial fulfillment of the requirements for a Masters of Philosophy in Development Studies at Massey University, Palmerston North, New Zealand - Entwistle, John M (Massey University, 2003)
The Lao PDR, a landlocked country, of 236 800 sq kms, with a population of 5,091,100, is situated between Thailand and Cambodia to the south, Vietnam to the east. China to the north, and Myanmar to the west. Lao is a geographically diverse country, which stretches along the Annamite chain to the Mekong River valley. There are 48 ethnic groups in the Lao PDR. The majority of which make up the Lao Loum (lowland Lao). Lao is one of the few remaining communist countries in the world today. Following the people's revolution in 1975 the Lao PDR was formed by the Lao Peoples Revolutionary Party, which currently remains the only political party in existence in the Lao PDR. Today the Party remains strong with a centralised government, though through a series of political reforms during the 1980s such as the introduction of the New Economic Mechanism the country has opened up to more international trade and investment. Entry into the World Trade Organisation (WTO) is now being considered following a submission made in 2000. The reproductive health of women in the Lao PDR is one of the top ten priorities of the Ministry of Health's Primary Health Care Policy. To assist with the implementation of the policy a National Family planning Program was established in 1991. While initial implementation of the program focussed on more densely populated areas in the more accessible provincial capitals along the Mekong River, women in remote rural communities are also being targeted. While the policy is to be commended for its aims, the implementation of activities to achieve its aims can at times be hindered by a lack of funding, poor infrastructure and communication and a lack of human resources. [FROM INTRODUCTION]
Keywords: Laos; Birth control clinics; Women; Social conditions